The Teacher Academic Buoyancy Scale: Is it possible to keep TABS on students' academic buoyancy? - Lisa Reidy; Scott Johnson; Diarmuid Verrier (International Journal of Assessment Tools in Education)
Academic buoyancy (AB) is the ability toovercome minor academic setbacks. However, although it seems as though teacherswould be well placed to comment on this characteristic in students, noteacher-report measure of AB exists. This study evaluates a teacher-reportversion of the widely used, student-report, Academic Buoyancy Scale (ABS).Confirmatory factor analysis supported the unifactorial nature of the TeacherAcademic Buoyancy Scale (TABS), and the scale showed excellent internalreliability. However, while there was some evidence for the criterion-relatedvalidity of the TABS, it showed very poor convergent validity with the ABS. Italso correlated better with academic achievement than should theoretically bethe case for a measure of AB. Further, ABestimates from the two measures were moderated by demographic characteristics:teachers rated girls and those not facing adversity as more buoyant, but theopposite was the case for self-reports. In sum, this study suggests asignificant disjunction between teacher- and self-reports of AB, and thatteacher estimates of AB are likely to be affected by salient, non-AB-related,student characteristics.